Embryonic development of larvae on the pleopods of the spiny lobster Panulirus polyphagus (Herbst) and the sand lobster Thenus orientalis (Lund) from Bombay waters - Kagwade, P V; Kabli, L M (Indian Journal of Fisheries, 2011)
Development of laivae to phyllosoma stage while still on the pleopods in the spiny lobster Panuliruspolyphagus (Herbsc)and the sand lobster Thenus orientalis (Lund)was studied. Growth of the larvae atthe time of hatching appeared more in the natural habitat than in the aquarium in both the species. The larvaehatched were in phyllosoma stage and not in naupliosoma orprephyllosoma stage. Differences describedin phyllosoma larvae of P. polyphagus and T. orientalis here may help in their identification